INTERNAL CONTROL, LEADERSHIP STYLE, AND WORK MOTIVATION OF EMPLOYEE PERFORMANCE AT PT KUSUMAHADI SANTOSA KARANGANYAR - LMS Kristiyanti; Abdul Haris Romdhoni; Ferdiana Dwi PR (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research discussed about the influences of internal control, leadership style, and work motivation on employee performance. This research aims to analyze the influences of internal control, leadership style, and work motivation on employee performance at PT Kusumahadi Santosa, Karanganyar. The research population is employees at PT Kusumahadi Santosa, Karanganyar. The method used to determine the sample is using technical solvents with several fixed criteria with a total amount of 92 samples. This research uses Statistical Product and Service Solutions (SPSS) version 25. The analysis method used is multiple linear regression analysis t test, F test and R2 test. Based on the analysis of the results, it is found that internal control has a significant effect on employee performance because its value is smaller than α = 0.05 that is 0.001 0,05. Keywords: Internal control, leadership style, work motivation and employee perfomance.